Acceleration algorithms for long-wavelength radiation integral in the annual simulation of radiative cooling in buildings. (January 2023) - Bu, Fan; Yan, Da; Tan, Gang; Sun, Hongsan; An, Jingjing
Abstract: Radiative cooling materials (RCMs) possess the capability of passively transferring heat from surfaces to the outer space through the atmospheric window via long-wavelength radiation and cool the surfaces to below the ambient temperature, showing excellent potentials for building energy efficiency. To adequately embody this passive cooling effect, especially for the spectra selective RCMs, quantitative spectrum integral is generally needed in building simulations. Nevertheless, the current integral process for hourly simulations may introduce massive computational time requirements when applied to large buildings or a cluster of buildings in cities, hindering its engineering applications. This study proposed four algorithms to simplify the integral process with evaluated accuracy and time-saving: the threshold algorithm, greedy algorithm, hierarchical clustering algorithm, and polynomial approximation algorithm. As a result, approximately 50–98% of the computational time consumption has been saved for the four RCMs. The polynomial approximation performs best compared with other three algorithms with an acceptable error in net long-wavelength radiation transfer of 0.16–4.33 W / m 2 . The optimized incorporation algorithm in this study could promote the simulation of RCMs in large city-scale application scenarios, such as urban heat island mitigation and heat wave impact.